A novel mechanism for high-altitude adaptation in hemoglobin of black-spotted frog (Pelophylax nigromaculatus) - Ma, Ming; Pu, Peng; Niu, Zhiyi; Zhang, Tao; Wu, Juan; Tang, Xiaolong; Chen, Qiang (Frontiers in Ecology and Evolution, 2023)
Understanding how animals living in highland adapt to extreme conditions is critical to evolutionary biology. In contrast to birds and mammals, little information was available on the adaptation mechanisms for O2 transport in high-altitude ectothermic vertebrates. Here we report for the first time on hematological parameters, amino acid sequences of α and β chains of hemoglobin (Hb), O2 affinity of purified hemoglobins (Hbs) and their sensitivities to anion allosteric effector (H+, Cl-, ATP) and temperature in the high-altitude (2292 m) black-spotted frogs (Pelophylax nigromaculatus) from the Qinghai-Tibet plateau (QTP) compared with the low-altitude (135 m) population. Our results showed that high-altitude black-spotted frogs exhibit significantly increased relative lung mass, hematocrit, and hemoglobin concentration, but significantly decreased body mass and erythrocyte volume, which could improve the blood O2 carrying capability. Compared with the low-altitude population, the purified Hbs of high-altitude black-spotted frogs possessed significantly higher intrinsic Hb-O2 affinity, similar low anion allosteric effector sensitivities, Bohr effects and temperature sensitivities. The elevated Hb-O2 affinity of highland frogs could maximize the O2 extraction from the lungs. Molecular dynamics simulations showed that the Gln123Glu substitution on α2 chain in highland frogs could form a hydrogen bond with 127Lys on α2 chain, resulting in the elimination of a hydrogen bond between 127Lys on α2 chain and 141Arg on α1 chain. This could weaken the interaction between two semirigid dimers (α1β1 and α2β2) and then lead to the high intrinsic Hb-O2 affinity in high-altitude black-spotted frogs.